The effect of oral analgesic premedication on the success rate of inferior alveolar nerve block for teeth with irreversible pulpitis: A randomized clinical trial - Negar Moghaddam; Ahmad Pirzadeh Ashraf; Fatemeh Bakhtiari; Fahime Mirzaali; Alireza Pournasrollah (Journal of Dental Materials and Techniques, 2024)
Objective: This study aimed to evaluate the effect of different premedication protocols on the success rate of the inferior alveolar nerve block (IANB) technique in mandibular molars with irreversible pulpitis.Methods: Two hundred and ten participants were randomly assigned into three groups (n=70) and received one of the following premedications 30 minutes before IANB injection: dexamethasone, pharmapain (containing acetaminophen, ibuprofen, and caffeine), and a placebo lactose capsule. Pain severity was evaluated with the Heft–Parker visual analog scale (VAS) before and 15 minutes after the injection, during dentin removal, and when inserting files into the root canal. The IANB injection was considered successful if VAS values after 15 minutes implied no pain or mild pain.Results:  IANB success rates were comparable in the dexamethasone (51.4%), pharmapain (55.7%), and placebo (41.4%) groups (P=0.222). Pain severity at baseline, 15 minutes post-injection, and during dentin removal was comparable among the groups (P>0.05). However, when inserting endodontic files, the mean pain severity in the pharmapain group was significantly higher than the dexamethasone group (10.27 ± 1.71 versus 7.38 ± 2.24; P=0.002). No significant difference was observed between the placebo with any of the study groups (P>0.05).Conclusions: Premedication with pharmapain (an anti-inflammatory agent) or dexamethasone (a corticosteroid) does not enhance the success rate of the IANB technique in mandibular molars with irreversible pulpitis compared to placebo. However, the use of dexamethasone was significantly more effective than pharmapain in reducing pain severity at inserting endodontic files.